2021
DOI: 10.35445/alishlah.v13i3.1156
|View full text |Cite
|
Sign up to set email alerts
|

Students' Writing Self-Efficacy, Writers' Block, and Academic Writing Performance: An Empirical Study in Eastern Indonesian Students

Abstract: This study was conducted to explore the students' perception related to the variables of writing self-efficacy, writers' block, and perceived academic writing performance. The researcher collected data from a University located in Papua Province. This research used an online questionnaire by employing simple random sampling. This study enrolled 280 students as respondents. The researchers used SPSS 23 to conduct a descriptive statistical analysis to determine the proportion of respondents based on the frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This finding suggests that despite having writer's block, students produced highquality written works. Prihandoko's (2021) study revealed that graduate students had writer's block while writing in English due to a lack of confidence, support, anxiety, fear of criticism, and instructors' demands on high-quality work. Several researchers employed certain teaching or writing techniques to reduce students' writer's block.…”
Section: Empirical Studies On Writer's Block In Academic Writing In E...mentioning
confidence: 99%
“…This finding suggests that despite having writer's block, students produced highquality written works. Prihandoko's (2021) study revealed that graduate students had writer's block while writing in English due to a lack of confidence, support, anxiety, fear of criticism, and instructors' demands on high-quality work. Several researchers employed certain teaching or writing techniques to reduce students' writer's block.…”
Section: Empirical Studies On Writer's Block In Academic Writing In E...mentioning
confidence: 99%